2003
DOI: 10.1038/sj.hdy.6800310
|View full text |Cite
|
Sign up to set email alerts
|

Genetic neighbourhood of clone structures in eelgrass meadows quantified by spatial autocorrelation of microsatellite markers

Abstract: Limited dispersal distances in plant populations frequently cause local genetic structure, which can be quantified by spatial autocorrelation. In clonal plants, three levels of spatial organization can contribute to positive autocorrelation; namely, the neighbourhood of (a) ramets, (b) clone fragments and (c) entire clones. Here we use data from an exhaustive sampling scheme on a clonal plant to measure the contribution of the neighbourhoods of each distinct clonal structure to total spatial autocorrelation. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 56 publications
4
46
0
2
Order By: Relevance
“…Spatial autocorrelation analysis is indicated for quantifying the component of genetic structure due to limited dispersal (Hämmerli & Reusch 2003). Our predictions on restricted dispersal in the species, based on its presumed philopatric larval behaviour , Mariani et al 2006, have been confirmed by autocorrelation statistics (Fig.…”
Section: Spatial Population Structuresupporting
confidence: 48%
See 1 more Smart Citation
“…Spatial autocorrelation analysis is indicated for quantifying the component of genetic structure due to limited dispersal (Hämmerli & Reusch 2003). Our predictions on restricted dispersal in the species, based on its presumed philopatric larval behaviour , Mariani et al 2006, have been confirmed by autocorrelation statistics (Fig.…”
Section: Spatial Population Structuresupporting
confidence: 48%
“…Since populations were relatively small and spatial autocorrelation has been reported to strongly depend on the scale and intensity of sampling (Hämmerli & Reusch 2003), we collected sponge fragments from all the individuals along each rocky wall (n = 27, n = 13 and n = 30 for Walls 1, 2 and 3, respectively). There were no individuals in the rocky areas between walls.…”
Section: Methodsmentioning
confidence: 99%
“…To date, meadow genetic structure and genetic similarity among pairs of ramets have been analysed as a function of their pairwise distance in only a few seagrass species. A positive spatial autocorrelation of kinship coefficients was found at a distance of 2 to 5 m and 2 m in the monoecious Zostera marina and Z. noltii, respectively (Hämmerli & Reusch 2003b, Coyer et al 2004, and at a distance of 10 to 16 m in the dioecious Cymodocea nodosa (Ruggiero et al 2005b).…”
Section: Introductionmentioning
confidence: 92%
“…Both are affected by shoot density of the meadow, which itself can become a recruitment barrier (Duarte et al 2006, Neiva et al 2012. Mosaic patterns of Zostera marina genotypes, attributed to sporadic recruitment and limited dispersal, have been documented in Brittany (Becheler et al 2010) and Schleswig-Holstein (Hämmerli & Reusch 2003). Both Medby and Sørkjosen are dense meadows, suggesting that recruitment may be limited.…”
Section: Substructure Within Meadows -Stochastic Processes or Habitatmentioning
confidence: 99%
“…Meadows may be heterogeneous as a consequence of temporal admixture events of repeated recruitment through time (originally proposed by Petit et al 2003for oaks, Becheler et al 2010; limited dispersal of pollen and seeds, leading to patchiness (Hämmerli & Reusch 2003); and local habitat selection (Oetjen & Reusch 2007, Oetjen et al 2010, Winters et al 2011. Alternatively, they can be homogeneous as a consequence of dominance by a few large genets/clones (Reusch et al 1999, Coyer et al 2008) and limited recruitment (Duarte et al 2006).…”
Section: Introductionmentioning
confidence: 99%